Analisis Pengaruh Tingkat Pendidikan dan Pengangguran terhadap Angka Kemiskinan di Kabupaten Lampung Timur Tahun 2012-2022 - Fajar Hamdan Nugraha; Prayoga Rahkmat Pratama; Yoga Hasbi Assidiq; Misfi Laili Rohmi (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to describe how the level of education and unemployment influence poverty in East Lampung district. This research focuses on data for the period 2012 to 2022, using a multiple linear regression data processing approach where the results of the f test show that simultaneously The influence of education level and unemployment has a significant influence on poverty in East Lampung district, the education level variable has a significant negative effect on poverty while the unemployment variable has no influence on poverty in East Lampung district. It is hoped that this research can help government policies to minimize the occurrence of poverty, unemployment and motivate the population to continue to be highly educated so that the amount of poverty is reduced and can increase the value of the population's income and increase the regional GDP of East Lampung district.